Odpowiedzi

  • Użytkownik Zadane
2010-02-16T15:33:52+01:00
A) 2x+5=14,8+(x-3)
2x+5=14,8+x-3
x+5=11,8
x=6,8

b)1/4x-(4+1/2x)=-2
¼x-4-½x=-2
¼x-4-2/4x=-2
-¼x=2
-x=8
x=-8

c)0,2-(10-3x)=3+2(x-1)
0,2-10+3x=3+2x-2
-9,8+3x=2x+1
x=10,8

d)x=-9+16
x=7

e)-x=-13-27
-x=-40
x=40

f)7/9x=-16 1/3
7/9x=-16 3/9
x=-147/9 * 9/7
x=-21
g)2(3-x)-4(x-5)=2x+2
6-2x-4x+20=2x+2
36-6x=2x+2
-8x=38
x=4¾
h) 1/3(-6x+9)-4=-5(x+1)
-2x+3-4=-5x-5
-2x-1=-5x-5
3x=-4
x-¾

i)4/9x-2=5/12-1 1/3
4/9x-2=5/12-4/3 /*12
16/3x-24=5-16
16/3x-24=-11
16/3x=13
x=39/16=2 7/16